2006
DOI: 10.1136/jcp.2005.035907
|View full text |Cite
|
Sign up to set email alerts
|

Presence of mouse mammary tumour-like virus gene sequences may be associated with morphology of specific human breast cancer

Abstract: Background: Mouse mammary tumour virus (MMTV) has a proven role in breast carcinogenesis in wild mice and genetically susceptible in-bred mice. MMTV-like env gene sequences, which indicate the presence of a replication-competent MMTV-like virus, have been identified in some human breast cancers, but rarely in normal breast tissues. However, no evidence for a causal role of an MMTV-like virus in human breast cancer has emerged, although there are precedents for associations between specific histological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…These assessments were categorized into MMTV-positive and MMTV-negative breast cancer specimens. This is an extension of our previous studies (28). …”
Section: Histologysupporting
confidence: 50%
See 1 more Smart Citation
“…These assessments were categorized into MMTV-positive and MMTV-negative breast cancer specimens. This is an extension of our previous studies (28). …”
Section: Histologysupporting
confidence: 50%
“…At low magnification MMTV-associated mouse mammary tumors do have different characteristics from human breast cancers; however, in some invasive breast cancers, the similarities can be striking in some breast cancers at a cellular level (28). Wellings (44) observed these similarities ∼30 years ago.…”
Section: Interpretation Of the Datamentioning
confidence: 83%
“…Lawson et al (2006) reported present of MMTV-like virus env DNA in37.3% of 59 human breast cancer patients. They conclude that some breast cancers not only are positive for MMTV-like env DNA but also have histological similarities to MMTVassociated mammary tumor of mice.…”
Section: 2945 Lack Of Pcr Detection Of Mmtv In Iranian Breast Cancersmentioning
confidence: 98%
“…A virus called MMTV-like virus has about 95% sequence homology to MMTV (Lawson et al, 2006). There is controversial evidence on the probable etiologic role of MMTV-like virus on the development of human breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that this virus is transmitted through breast milk to the offspring, while exogenous virus can infect adults [297,298]. Recently, several studies from different groups have reported the detection of MMTV-like sequences in up to 60% of breast biopsies from women with breast cancer and gynecomastia, a possible premalignant condition [299][300][301][302][303]. However, despite many efforts researchers have not agreed on the origins of these viral sequences.…”
Section: Mouse Mammary Tumor Virusmentioning
confidence: 99%